2017
DOI: 10.1111/bph.13733
|View full text |Cite
|
Sign up to set email alerts
|

Role of inducible nitric oxide synthase in endothelium‐independent relaxation to raloxifene in rat aorta

Abstract: Raloxifene-mediated vasorelaxation in rat aorta is independent of a functional endothelium and is mediated by oestrogen receptors and NF-κB. This effect is mainly mediated through an enhanced production of NO, cGMP and nitrite, via the induction of iNOS and inhibition of calcium influx through Ca channels in rat aortic smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In this study, nitric oxide (NO) and tumor necrosis factor (TNF)‐α were used as indicators to assess the anti‐inflammatory activity of ASR . Treatment by ASR significantly reduced NO and TNF‐α release in lipopolysaccharide (LPS)‐ and adenosine triphosphate (ATP)‐stimulated BV2 microglia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, nitric oxide (NO) and tumor necrosis factor (TNF)‐α were used as indicators to assess the anti‐inflammatory activity of ASR . Treatment by ASR significantly reduced NO and TNF‐α release in lipopolysaccharide (LPS)‐ and adenosine triphosphate (ATP)‐stimulated BV2 microglia.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,17 In this study, nitric oxide (NO) and tumor necrosis factor (TNF)-α were used as indicators to assess the anti-inflammatory activity of ASR. 18,19 Treatment by ASR significantly reduced NO and TNF-α release in lipopolysaccharide (LPS)-and adenosine triphosphate (ATP)-stimulated BV2 microglia. Using benzylamine as a substrate, in vitro enzyme inhibition assay results showed that the IC 50 of ASR to MAO-B was 1.611 mg/mL, suggesting that this TCM formula contains compounds with MAO-B inhibitory activity.…”
mentioning
confidence: 99%
“…NO is an intracellular messenger discovered in recent years, which may play a role in information transmission in the central nervous system (Wong et al, 2017). NO can be produced by L-arginine catalyzed by nitric oxide synthase (NOS) (Grasemann et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In their recent article, Wong et al . () report a number of observations and conclusions that are difficult to reconcile, both methodologically and mechanistically. The authors state that in endothelium‐denuded aortic rings of male Sprague–Dawley rats, raloxifene at concentrations of 1 μM caused ‘a time‐dependent relaxant response for 3 h’ that was mediated by inducible NOS (iNOS or NOS2).…”
Section: Nomenclature Of Targets and Ligandsmentioning
confidence: 99%